2021
DOI: 10.2147/cmar.s312828
|View full text |Cite
|
Sign up to set email alerts
|

Role of Systemic Inflammatory Reaction in Female Genital Organ Malignancies – State of the Art

Abstract: Systemic inflammatory reaction (SIR) is an unfavorable prognostic factor in many malignancies and has a role in all stages of the neoplastic process: initiation, promotion, and disease progression. Analysis of SIR can be performed by assessing indicators (eg, lymphocyte-to-neutrophil, platelet-to-lymphocyte, and monocyte-to-neutrophil ratios) and products of neutrophils and lymphocytes (ie, the systemic immune-inflammation index), or by examining the relationship between levels of C-reactive protein and albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 146 publications
0
10
0
Order By: Relevance
“…The neutrophil to lymphocyte ratio and platelet to lymphocyte ratio are two biomarkers of systemic inflammation that have increasingly gained interest in the diagnosis of a variety of cardiovascular diseases [ 30 , 31 , 32 ], diabetes [ 33 , 34 , 35 ], inflammatory diseases [ 36 , 37 ], and malignancies [ 38 , 39 ]. In our review, we found higher mean values of NLR in periodontitis patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil to lymphocyte ratio and platelet to lymphocyte ratio are two biomarkers of systemic inflammation that have increasingly gained interest in the diagnosis of a variety of cardiovascular diseases [ 30 , 31 , 32 ], diabetes [ 33 , 34 , 35 ], inflammatory diseases [ 36 , 37 ], and malignancies [ 38 , 39 ]. In our review, we found higher mean values of NLR in periodontitis patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the systemic inflammatory response to tumor cells, especially white blood cells and platelets, have drawn attention as valuable prognostic biomarkers [ 11 ]. The systemic inflammatory markers, i.e., neutrophil–lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR), have been used as prognostic biomarkers in various types of cancers [ 14 , 15 , 16 , 17 , 18 ]. These serum inflammatory markers are easily available because they can be retrieved from routine blood tests [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of the three parameters/indices/ratio NLR, PLR, and LMR as markers of systemic inflammation requires the exposure of the scientific support regarding the inflammation-neoplasia interference, at least regarding the existence of inflammation as a defense process against neoplasia and only tangentially as a process which intervenes in carcinogenesis. 21 , 22 The appearance and development of the ovarian neoplasm, as a consequence of the existence of a chronic regional inflammation (usually located in the distal part of the Fallopian tube, or at the level of the ovarian epithelium) has as its pathogenic cause the installation of local oxidative stress, just like the evolution of any other inflammatory process, regardless of location. 23 , 24 At any evolutionary moment of carcinogenesis (installation, local invasion or metastasis), the inflammatory process persists, developing together with the immune system, as anti-neoplasia defense systems.…”
Section: Methodsmentioning
confidence: 99%